1985
DOI: 10.1002/jcp.1041220116
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsiveness of cultured suckling and adult rat hepatocytes to growth‐promoting factors: Entry into s phase and mitosis

Abstract: The capacity of suckling and adult rat hepatocytes in culture to enter into S phase and mitosis in response to EGF, insulin, and glucagon was measured. Both cell types were isolated in high yield and purity and cultured in the absence of serum under identical conditions. At the time of isolation, suckling rat hepatocytes were all diploid and in the G1 phase of the cell cycle. Adult rat hepatocytes constituted a population of mixed ploidy level, as shown by flow cytometry. Upon stimulation, both suckling and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
(53 reference statements)
2
14
0
Order By: Relevance
“…These conditions allow the majority of cells to undergo DNA synthesis and mitosis while still retaining measurable TAT activity and other hepatic functions (2). Hepatocytes and nonparenchymal cells in the primary cultures were discriminated by differential immunostaining for cytokeratin A and vimentin, respectively (1). In all cases, hepatocytes comprised >95% of the population.…”
Section: Methodsmentioning
confidence: 99%
“…These conditions allow the majority of cells to undergo DNA synthesis and mitosis while still retaining measurable TAT activity and other hepatic functions (2). Hepatocytes and nonparenchymal cells in the primary cultures were discriminated by differential immunostaining for cytokeratin A and vimentin, respectively (1). In all cases, hepatocytes comprised >95% of the population.…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes cultured for various periods were treated with 0.12 mM colchicine for 8 h, fixed in methenokacetic acid (3:1), and then stained with Hoechst 33258 (Chen, 1977;Baribault et al, 1985). The proportion of hepatocytes in metaphase was evaluated by counting the percentage of hepatocyte mitoses in six separate fields (a total of about 500 cells).…”
Section: Mitosismentioning
confidence: 99%
“…EGF, insulin, and glucagon are growth-promoting factors of rat hepatocytes both in vivo (Bucher et al, 1978;Bucher and Weir, 1976;Bucher and McGowan, 1979) and in primary culture (Richman et al, 1976;McGowan et al, 1981;McGowan and Bucher, 1983;Friedman et al, 1981;Hasegawa et al, 1982;Marceau et al, 1982;Baribault et al, 1985). Glucocorticoids such as dexamethasone can modulate the proliferation of various cell types and promote the differentiation of various tissues (Guerriero and Florini, 1980;Belanger et al, 1981).…”
mentioning
confidence: 99%
“…Likewise Parzefall et al (19) and Tomita et al (20) induced DNA synthesis and mitosis in the presence of sera and McGowan et al (21) and McGowan and Bucher (22) reported DNA synthesis and mitoses in a serum-free medium after plating in serum. In a totally serum-free culture system, Baribault et al (23) found significant mitoses but only in hepatocytes from suckling rats and very few from adult rats. Hasegawa et al (24) reported time lapse cinematography of mitoses in cells from adult rats cultured in a serumfree medium, but only if the calcium concentration was reduced below 0.4 mM and a trypsin inhibitor was used.…”
mentioning
confidence: 99%